Traffic Safety Council of Zimbabwe Key Performance Indicator Network Monitoring System - Maramba, Oliver (Midlands State University, 2020)
This project concentrates on developing the TSCZ Key Performance Indicator Network Monitoring System, which was seen necessary after it was discovered that the manual system that was being used for network troubleshooting and monitoring had weaknesses. The organization could not ascertain bandwidth required hence this resulted in acquiring less or more bandwidth than the optimum from the service providers, as there was no yardstick for benchmarking. Consequently, the organization suffers slow network speed, network congestion, service disruption because of that. In addition to that, the manual system was also not effective has there was unavailability of network performance indicators such as network speed, bandwidth utilization in the time of network troubleshooting. A working and lasting solution to the problems was created and in-house development was considered as the best alternative .A feasibility study was carried out to assess if the project was technically, economically and operationally feasible. It was then seen favorable to continue with the project since deemed feasible. Information was gathered using interviews, questionnaires and background reading to gather functional requirements of the system and problems faced by users with the old system. The design phase was conducted which included the system dataflow design, interface as well as database tables design. The TSCZ Key Performance Indicator Network Monitoring System was developed using ASP.Net and C# with SQL Server Database. The system developed was tested thoroughly using unit testing, sub system testing, acceptance testing, validation and verification. This was carried out to see that system was working without errors whilst the specifications and objectives of the system were met. The system conversion methodologies were evaluated and a parallel changeover was recommended to install the system as it gives users time to familiarize with the system. Also this means that anomalies can be rectified during this period. Risk were identified together with their counter measures. The organization will have backup from the old system so it can revert to the old system if the new system fails. Maintenance strategies were discussed and it was seen necessary to use them all to ensure the continuity of the system, efficiency and effectiveness. Recommendations were made so that the system will make TSCZ a good environment for work through introducing a chat facility.